Penetapan Hak Asuh Anak Pasca Perceraian Berdasarkan Asas Kepentingan Terbaik Anak - Syahan Nur Muhammad Haiba; Anjar Sri Ciptorukmi Nugraheni (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
In Indonesian positive law, only the KHI states that child custody falls to the mother. Other regulations only state that both parents are still obliged to look after their children without providing an explanation to whom child custody is given after divorce. In child custody decisions, several decisions were found that gave child custody to the mother, but also decisions were found that gave child custody to the father. This causes legal uncertainty in determining child custody after divorce. This research aims to analyze the most appropriate indicators of the judge's consideration in decisions regarding child custody based on the principle of the child's best interests. The research method used is prescriptive normative legal research using a conceptual approach. The results of the research show that there are several indicators that can be used in considering determining child custody, namely, child welfare, parental behavior, coordination between parents, and distribution of parental time. If it is felt that other indicators are needed, the judge can add these indicators as long as they are in accordance with the principle of the child's best interests.